Can Digit Ratio (2D:4D) Be Indicative of Predispositions to Autoimmune Thyroid Diseases in Women - Hashimoto Thyroiditis and Graves’ Disease? - Święchowicz, Barbara; Kasielska-Trojan, Anna; Manning, John T.; Antoszewski, Bogusław (Frontiers in Endocrinology, 2022)
Hashimoto thyroiditis (HT) and Graves’ disease (GD) are autoimmune thyroid diseases (AITD), which occur much more frequently in women than in men. Estrogen receptors are found in the thyroid gland and can modulate the gland's function. Digit ratio (2D:4D) is thought to be a negative correlate of prenatal testosterone and a positive correlate of prenatal estrogen. This study aimed to examine a relationship between right and left 2D:4D in women with HT and GD. The cross-sectional study included 106 women with autoimmune thyroid disease: 73 women diagnosed with Hashimoto thyroiditis and 33 women with Graves’ disease, together with 70 healthy women as controls. Second and fourth digit length, weight, height were measured directly, and 2D:4D and BMI were calculated. Compared to controls, right and left 2D:4D were significantly higher in women with HT and lower in women with GD, the effects were higher for right 2D:4D. The mean length of right 4D was significantly lower in the examined women with HT than in GD. Higher right and left 2D:4D in women with HT suggests that prenatal exposure to high levels of estrogens relative to testosterone may play a role in the development of this disease. Lower right and left 2D:4D in women with GD suggest a role of high prenatal androgens relative to estrogens in Graves’ disease pathogenesis.